A Systematic Review of Outcomes after Revision Amputation for Treatment of Traumatic Finger Amputation. Issue 1 (July 2015) - Yuan, Frank; McGlinn, Evan P.; Giladi, Aviram M.; Chung, Kevin C.
Abstract : Background: Revision amputation is often the treatment for traumatic finger amputation injuries. However, patient outcomes are inadequately reported, and their impact is poorly understood. The authors performed a systematic review to evaluate outcomes of revision amputation and amputation wound coverage techniques. Methods: The authors searched all available English literature in the PubMed and Embase databases for articles reporting outcomes of nonreplantation treatments for traumatic finger amputation injuries, including revision amputation, local digital flaps, skin grafting, and conservative treatment. Data extracted were study characteristics, patient demographic data, sensory and functional outcomes, patient-reported outcomes, and complications. Results: A total of 1659 articles were screened, yielding 43 studies for review. Mean static two-point discrimination was 5.0 ± 1.5 mm ( n = 23 studies) overall, 6.1 ± 2.4 mm after local flap procedures, and 3.8 ± 0.4 mm after revision amputation. Mean total active motion was 93 ± 8 percent of normal ( n = 6 studies) overall. It was 90 ± 9 percent of normal after local flap procedures and 95 percent of normal after revision amputation. Seventy-seven percent of patients reported cold intolerance after revision amputation. Ninety-one percent of patients (217 of 238) reported "satisfactory" or "good/excellent" ratings regardless of treatment. Conclusions: Revision amputation and conservative treatments result in better static two-point discrimination outcomes compared with local flaps. All techniques preserve total active motion, although arc of motion is slightly better with revision amputation. Revision amputation procedures are frequently associated with cold intolerance. Patients report "satisfactory, " "good, " or "excellent" ratings in appearance and quality of life with all nonreplantation techniques.